Testosterone therapy to prevent type 2 diabetes mellitus in at‐risk men (T4DM): Design and implementation of a double‐blind randomized controlled trial. Issue 4 (4th January 2019) - Wittert, Gary; Atlantis, Evan; Allan, Carolyn; Bracken, Karen; Conway, Ann; Daniel, Mark; Gebski, Val; Grossmann, Mathis; Hague, Wendy; Handelsman, David J.; Inder, Warrick; Jenkins, Alicia; et al.
Abstract : Background: Low circulating testosterone is associated with an increased risk of developing type 2 diabetes (T2DM) in overweight men with impaired glucose tolerance (IGT). Aims: To determine in a multi‐centre, double‐blinded placebo‐controlled randomized trial whether testosterone treatment combined with lifestyle intervention (Weight Watchers) relative to lifestyle intervention alone reduces T2DM incidence and improves glucose tolerance at 2 years. Study population: Overweight or obese men aged 50‐74 years with a serum testosterone of ≤14 nmol/L and IGT or newly diagnosed T2DM established by an oral glucose tolerance test (OGTT). Setting, drug and protocol: Six Australian capital city‐based tertiary care centres. Participants were randomized 1:1 and injected with testosterone undecanoate (1000 mg/4 mL) or vehicle (4 mL castor oil), at baseline, 6 weeks and 3‐monthly thereafter. Primary endpoints: (a) Proportion of participants with 2‐hour OGTT ≥11.1 mmol/L at 2 years, and (b) a difference at 2 years ≥0.6 mmol/L in the mean 2‐hour OGTT glucose between treatments. Secondary endpoints: Fasting insulin, HbA1c, body composition, maximal handgrip strength; sexual function and lower urinary tract symptoms; serum sex steroids and sex hormone binding globulin; mood and psychosocial function; adherence to lifestyle intervention; and healthcare utilization and costs. Safety: Overseen by an Independent Data Safety Monitoring Committee. Haematocrit, lipids and prostate‐specific antigen (PSA) are assessed 6‐monthly and information relating to haematological, urological and cardiovascular adverse events from each clinic visit. Sub‐studies: (a) Changes in bone density and micro‐architecture, (b) motivation and behaviour, (c) telomere length, (d) extended treatment up to 4 years, and (e) hypothalamo‐pituitary testicular axis recovery at treatment end.